O significado do diagnóstico do diabetes mellitus gestacional na perspectiva de um grupo de grávidas hospitalizadas - Pessoa, Sarah Maria Fraxe (2008)
Gestational Diabetes Mellitus is one of the most frequent metabolic syndromes and often requires hospitalization.The professional exercise dedicated to the care of pregnant women with DMG showed social and psycological problems caused by diagnosis and obligation of hospitalization, leading to the following assumption: the diagnosis of DG unexpected and prolonged hospitalization bring feelings of fear of not reaching the end of pregnancy and have a healthy baby. These moments are also permeated of concerns regarding to the absence of the children who stayed at home. The experiences shared with these women encouraged the development of this research, which is proposed to understand the meaning of the diagnosis and hospitalization in the perspective of a group of pregnant women with GDM.The phenomenological study was conducted in the obstetrical clinic of Maternidade Escola Assis Chateaubriand, Federal University of Ceará, in Fortaleza/Ceará. Twelve women hospitalized for the first time during pregnancy participated in the research. Information obtained between April and October, 2007, were extracted from medical records, semi-structured interviews, practice of art-therapy and daily notes from a field diary. Such information was also organized on the method of Colaizzi and analyzed based on the scholars of existential phenomenology, art-therapy and gestational diabetes. The study showed that to have gestational diabetes means: 1. living experiences that bring happiness, welfare and changes in attitude, as the pleasant feeling of pregnancy and be a mother; the sense of happiness due the chances of treatment, control and even cure of the disease, and the opportunity to be with each other during hospitalization and 2. living experiences of suffering emerged from the impact of diagnosis, as the fear of death, despair, sadness, anxiety, distress, insecurity and depression. The comprehension of the phenomenon confirmed the assumption formulated and added other facets to the same phenomenon, revealing the need for a new look to the care of pregnant women hospitalized with gestational diabetes mellitus which prioritize the use of entertainment and expressive resources; the permission for the children to visit their mothers during hospitalization; and implementation of educational activities within the units of hospitalization. From the speeches of the women it was observed that such strategies make the period of hospitalization more quiet and receptive, which would help these women to realize themselves as Human Beings with multiple possibilities.